2007
DOI: 10.1002/ldr.830
|View full text |Cite
|
Sign up to set email alerts
|

Sediment‐bound nutrient export from micro‐dam catchments in Northern Ethiopia

Abstract: The losses in soil nutrients (nitrogen (N), available phosphorus (P av ), organic carbon (OC), potassium (K), calcium (Ca) and magnesium (Mg)) in the catchment and the storage in the reservoir as a result of sediment delivery were assessed in 13 catchments/reservoirs in Tigray, Northern Ethiopia. This specifically dealt with factors controlling the losses, the fertility status of the deposited sediment, the nutrient export (NE) rates and associated costs.Enrichment ratio (ER) values >1 were observed for the pl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
57
3
3

Year Published

2007
2007
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 89 publications
(69 citation statements)
references
References 25 publications
5
57
3
3
Order By: Relevance
“…This is within the range of sediment yields measured in other catchments in the Tigray highlands (1·9 -18·2 t ha −1 y −1 ), using reservoir sedimentation rates (Nigussie et al, 2007). The sediment delivery ratio…”
Section: Soil Loss and Sediment Movement -The Horizontal View Measursupporting
confidence: 77%
“…This is within the range of sediment yields measured in other catchments in the Tigray highlands (1·9 -18·2 t ha −1 y −1 ), using reservoir sedimentation rates (Nigussie et al, 2007). The sediment delivery ratio…”
Section: Soil Loss and Sediment Movement -The Horizontal View Measursupporting
confidence: 77%
“…Fonseca et al (1998) investigated the trapped sediments of two reservoirs in Portugal and found that sediments of both reservoirs had high nutrient levels, with values exceeding those of the original soils. Haregeweyn et al (2008) report similar results for 13 reservoirs in the semi-arid northern Ethiopian highlands, where sediments from the reservoirs were richer in nutrients than the original soils from where they eroded. This enrichment in nutrients is associated with the preferential transport of nutrients bound to finer soil fractions and the dissolution of parent material and its transport via runoff ).…”
Section: Iii3 Problems Related To Nutrients and Ecologysupporting
confidence: 58%
“…Furthermore, the nutrient-rich sediments in reservoirs can cause eutrophication and water quality problems, particularly in drinking water reservoirs (Lahlou 1996;Fonseca et al 1998). Dredging the sediments and using it as fertilizer could provide a solution, if this is economically feasible (Fonseca et al 1998;Haregeweyn et al 2008) yet only if concentrations of pesticides and herbicides are within acceptable ranges! !.…”
Section: Iii3 Problems Related To Nutrients and Ecologymentioning
confidence: 99%
“…los flujos laterales de C. Jacinthe et al, 2004;Moorman et al, 2004;Haregeweyn et al, 2008;Starr et al, 2008;Boix-Fayos et al, 2009;Juárez et al, 2011).…”
Section: Figura 3 Flujos De C Inducidos Por Procesos Erosivos Se Prunclassified